2011
DOI: 10.1021/ja2097089
|View full text |Cite
|
Sign up to set email alerts
|

A 1,3-Dihydro-1,3-azaborine Debuts

Abstract: We present the first synthesis and characterization of a 1,3-dihydro-1,3-azaborine, a long-sought BN isostere of benzene. 1,3-Dihydro-1,3-azaborine is a stable structural motif with considerable aromatic character as evidenced by structural analysis and its reaction chemistry. Single crystal X-ray analysis indicates bonding consistent with significant electron delocalization. 1,3-Dihydro-1,3-azaborines also undergo nucleophilic substitutions at boron and electrophilic aromatic substitution reactions. In view o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 42 publications
3
82
0
8
Order By: Relevance
“…[94,95] The premise here is that in these carbon-boron-nitrogen heterocycles (see the bottom of Figure 17 for an example of a CBN), the exothermic release of hydrogen from the BN segment of a molecule can be coupled to and offset the endothermic release of hydrogen from the CC segment of the same molecule. If the kinetics of release can be made to be similar for the two channels, then the thermodynamics of hydrogen release may be coupled, resulting in principle in a nearthermoneutral release material.…”
Section: E Ionic Liquid/ab Mixturesmentioning
confidence: 99%
“…[94,95] The premise here is that in these carbon-boron-nitrogen heterocycles (see the bottom of Figure 17 for an example of a CBN), the exothermic release of hydrogen from the BN segment of a molecule can be coupled to and offset the endothermic release of hydrogen from the CC segment of the same molecule. If the kinetics of release can be made to be similar for the two channels, then the thermodynamics of hydrogen release may be coupled, resulting in principle in a nearthermoneutral release material.…”
Section: E Ionic Liquid/ab Mixturesmentioning
confidence: 99%
“…[5] On the other hand, we showed that treatment of 1 with acetic acid readily furnished the B-OAc-substituted product. [6] Encouraged by this preliminary finding, we envisioned that 1,3-azaborine 1 could be converted to B-substituted derivatives under acidic conditions.…”
Section: Nih Public Accessmentioning
confidence: 86%
“…[4] Not surprisingly, its development has lagged the other azaborines in the series. The first synthetic example of a 1,3-azaborine debuted in late 2011, [5] and the diversity of synthetically accessible 1,3-azaborines remains very limited to date. …”
mentioning
confidence: 99%
See 2 more Smart Citations